Kecerdasan Emosional, Motivasi Berprestasi, dan Self-esteem serta Pengaruhnya terhadap Kepuasan Kerja Guru - Hartini, Hartini -; N, Normiyati; Wardhana, Aditya (Jurnal Manajemen, 2022)
This study aims to determine and analyze:1) the effect of emotional intelligence on teaher’s job satisfaction, 2) the effect of achievement motivation on teaher’s job satisfaction. 3) the effect of self-esteem on teaher’s job satisfaction. 4) the effect of simultaneous emotional intelligence, achievement motivation, and self-esteem on teaher’s job satisfaction. This type of research is quantitative research with expost facto approach. This research was conducted at Public Elementary School in Sub-districts Kindang. The population in this study were all teacher totaling 199 people. The sample of the study was 67 teachers. Data collection techniques using questionnaire and documentation techniques. Data analysis techniques are carried out after data from all respondents or other data sources are collected with analytical activities including test prerequisite analysis and hypothesis testing (multiple linear regression). The results of the study show that: 1) emotional intelligence had a positive and significant effect on teaher’s job satisfaction, 2) achievement motivation had a positive and significant effect on teaher’s job satisfaction. 3) self-esteem had a positive and significant effect on teaher’s job satisfaction. 4) overall, emotional intelligence, achievement motivation, and self-esteem had a positive and significant effect on teaher’s job satisfaction.